ANEMIA DI KALANGAN MAHASISWI: PREVALENSI DAN KAITANNYA DENGAN PRESTASI AKADEMIK - Anindya Mar'atus Sholikhah; Yetty Septiani Mustar; Agus Hariyanto (UNUSA Press, 2021)
Anemia is still considered as a serious health problem worldwide that requires large attention. Anemia does not only have an impact on health but also affect student achievement. This study aims to identify the prevalence of anemia among female university students in Surabaya and its relationship to academic achievement. This is an observational analytic study with cross-sectional design, involving 92 respondents who were selected using a consecutive sampling method. Data collected by using a questionnaire to obtain respondent characteristics, grade point average (GPA), and menstrual patterns. The measurement of hemoglobin levels carried out using the cyanmethemoglobin method. The results showed that the prevalence of anemia among female students was still quite high and there was a significant relationship between the incidence of anemia and students’ academic achievement measured by grade point average. Female students are one of the groups that are susceptible to anemia, so it is essential to make various efforts to improve Hb levels by increasing the intake of foods high in iron.